Tetany despite normocalcaemia and normomagnesaemia following parathyroidectomy. Issue 744 (October 1987) - Fonseca, V. A.; Bloom, R. D.; Dick, R.; Dandona, P.
Abstract : Two patients with long-standing hyperparathyroidism due to a parathyroid adenoma are described. Both had severe osteitis fibrosa cystica and a proximal myopathy. Both were treated with alfacalcidol (2 micrograms/day) prior to and following parathyroidectomy, and infused with calcium gluconate following the operation. Plasma total and ionized calcium and magnesium concentrations were maintained within the normal range. However, both developed tetany in the postoperative period in spite of normal ionized calcium and magnesium concentrations. Tetany continued for 4 weeks in one patient and for longer in the other. Prolonged hypercalcaemia may result in a state of neuromuscular excitability following parathyroidectomy even at high normal concentrations of ionized calcium.